1999
DOI: 10.1002/(sici)1098-2264(199902)24:2<105::aid-gcc2>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal FHIT transcripts found in both lung cancer and normal lung tissue

Abstract: Occurrence of abnormal transcripts of the FHIT (fragile histidine triad) gene has been reported in various types of cancer. On the other hand, aberrant transcripts are sometimes found in non-neoplastic tissues, so the relationship between the presence of abnormal transcripts of the FHIT gene and cancer pathogenesis is controversial. We investigated alterations in the FHIT locus, detected by nested reverse transcription-polymerase chain reaction and/or allelic status, in 88 primary lung cancers and normal lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The reported frequency of LOH at FHIT gene in NSCLC is between 20 and 70% of cases. 5,11,[17][18][19][20][21][22][23][24] Our results are similar to the highest frequency, with LOH in one or more microsatellites in 67.8% of 96 informative tumors. The differences between all series probably could be explained by the different markers used and the method of detection and evaluation of LOH.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The reported frequency of LOH at FHIT gene in NSCLC is between 20 and 70% of cases. 5,11,[17][18][19][20][21][22][23][24] Our results are similar to the highest frequency, with LOH in one or more microsatellites in 67.8% of 96 informative tumors. The differences between all series probably could be explained by the different markers used and the method of detection and evaluation of LOH.…”
Section: Discussionsupporting
confidence: 81%
“…Since when different groups use the same methods, the frequencies are similar around 60%. 11,12,18,22 Loss of immunoexpression of FHIT, the protein encoded by this gene, has been described in several 39 and it is higher than the frequency reported by others. 13,23,33,38 These discrepancies may be due to differences in immunohistochemical techniques, stain interpretation or different distributions of histological types.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In four cases, there were aberrant smaller-sized transcripts in addition to the normal transcript. In NSCLC, presence of both aberrant and normal FHIT transcripts were seen in 40% (11), 59% (22), and 100% tumors (23). Sequence analysis of aberrant products showed that majority of these products lacked either exon 5, which contains the start codon, or exon 8, containing the histidine triad motif important for its functional activity.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the suppressor activity of FHIT could be related with apoptosis and with the alteration of cell cycle regulator factors. Frequent allelic losses and homozygous deletions (8,9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), as well as the loss of heterozygosity in microsatellites located at the FHIT gene have been described at the FHIT locus in several human solid tumors arising from epithelial cells (13,19,20,(25)(26)(27)(28)(29)(30)(31)(32). Studies comparing FHIT expression with the status of the FHIT gene have shown significant concordance in a variety of malignancies.…”
Section: Introductionmentioning
confidence: 99%